Analisis Interaksi Sosial Kooperasi Teman Sebaya Dalam Menumbuhkan Motivasi Belajar Siswa Pada Pelajaran Sosiologi Di Kelas XI IPS 1 - Wijaya, Tri (Jurnal Pendidikan Sosiologi dan Humaniora, 2014)
This research was aim to analyze cooperation of social interaction among peers in order to improve students’ motivation in study in sociology subject in class XI Social 1 of Muhammadiyah 2 Senior High School Pontianak. Method that was used in this research was qualitative approach. The result of data analyze showed that the form of cooperation of social interaction in XI Social 1 was variated which group 3 achieved the form of cooperation of social interaction in high level, group 5 achieved cooperation of social interaction in middle level, and group 6 achieved cooperation of social interaction in beginning level. The level of students’ motivation in study in class XI Social 1 was good enough. It showed by group 3 and 5 were achieved satisfied level and group 6 achieved confidence level. Cooperation of social interaction among peers which can grow students’ motivation in study in class XI social 1 whether group 3, 5, and 6 showed antusiasm act and happiness during learning process grouply. Keywords : Cooperation Of Social Interaction, Peers, Motivation Of Study.